CHEMICAL COMPOSITIONS, ANTIOXIDANT CAPACITY OF TIGERNUT (Cyperus esculentus) AND POTENTIAL HEALTH BENEFITS - I., Ogunlade; Bilikis, A., Adeyemi; Olanrewaju, G., Aluko (European Scientific Journal, ESJ, 2015)
Tiger nut (Cyperus esculentus L.) considered as an intrusive weed in most countries but taken as snack in Nigeria was analyzed for proximate and mineral compositions using standard analytical techniques. Antioxidant activity of the methanolic extract was measured using 2, 2-diphenyl-1- picryhydrazyl (DPPH), while the total phenolic content was determined according to Folin-Ciocalteu method. The results revealed that the three forms of the tuber (dry, raw and roasted) as consumed had % moisture ranging from (12.57-43.84); protein (1.32-2.24); fat (1.44-1.54); ash (3.34- 6.69); crude fibre (16.14-17.14); and carbohydrate (30.58-62.79). The samples were significantly high in Na, K and Ca. Na-K ratio was also found to be less than 1 suggesting its suitability in formulating diets for hypertensive patients. Antioxidant activity of the samples ranged from 3.72- 5.90; 5.22-9.72; 11.63-16.10; and 15.95-23.00 % inhibitions at different levels of concentrations while total phenolic content ranged from (806.7- 1150.7) micromole GAE/g. The results indicate that the edible tubers which are used for non-alcoholic local beverage formulation, in medicine and cosmetic industry can be utilized to ‘mop up’ and scavenge free-radicals generated by essential metabolic body reactions and environmental pollutants. It is hoped that addition of tiger nut as side dish and adjunct in traditional diets will probably alleviate the symptoms associated with neurodegenerative and cardiovascular diseases.